Model Curriculum Development Local Wisdom on Industry 4.0: Education Indonesia - Wulandari, Desi; Rochim, Raudhotul Aulia; Hikmah, Saniyatul; Hidaayatullaah, Hasan Nuurul; Fehabutar, Daliana; Citra, Nina Fajriyah (National Dong Hwa University, 2024)
Rapid changes in technology affect curriculum changes. The Indonesian curriculum that is currently running, namely the independent learning curriculum (MBKM), provides an opportunity for researchers to study educational curriculum design. This research aims to analyze the development of the local wisdom curriculum in the Industrial Era 4.0, analyze the design of the local wisdom industry 4.0 curriculum against the curriculum that has been put forward by researchers, and analyze it in the independent learning curriculum. This type of research is a study of curriculum development design literature. The results of the analysis show that the Local Wisdom Industry 4.0 curriculum model is a curriculum model developed based on local wisdom with each curriculum implementation process structured starting from curriculum objectives, content, processes, outcomes, and evaluation processes implemented according to developments in the Industry 4.0 era. This model was developed by integrating the Tyler model curriculum and the Hawes model and emphasizing curriculum objectives and learning processes.